Conducting polyanilline based paints on hot dip galvanized low carbon steel for corrosion protection - Deshpande, P.; Vagge, S.; Jagtap, Sharmili; Khiarnar, R.; Kelkar, Sarika A.; More, Minal (Bulgarian Chemical Communications, 2012)
Conducting polyaniline based paints have been applied on hot dip galvanized low carbon steel samples. The corrosion protection performance of these paint coatings was evaluated by using Tafel plots and impedance spectroscopy. It was found that the paint coatings offered significant corrosion protection to hot dip galvanized low carbon steel in aqueous 3.5 wt % NaCl solution.
Keywords: Conducting polyaniline based paints; corrosion prevention; hot dip galvanized low carbon steel

Molecular dynamics simulation of phosphoric acid doped monomer of polybenzimidazole: a potential component polymer electrolyte membrane of fuel cell - Pahari, Swagata; Choudhury, Chandan Kumar; Pandey, Prithvi Raj; More, Minal; Venkatnathan, Arun; Roy, Sudip (Journal of Physical Chemistry B, 2012)
Phosphoric acid doped polybenzimidazole is promising electrolyte membranes for high temperature (100 degrees C and above) fuel cells. Proton conduction is governed by the amount of phosphoric acid content in the polymer membrane. In this present work, we perform molecular dynamics simulations on phosphoric acid doped 2-phenyl-1H,1'H-5,5'-bibenzo[d]imidazole (monomer unit of polybenzimidazole) to characterize the structural and dynamical properties at varying phosphoric acid content and temperature. From the structural analysis, we have predicted the arrangement of the phosphoric acids, formation of H-bonds in the system, and the contribution of different atoms toward H-bonding. We have also examined the stacking of 2-phenyl-1H,1'H-5,5'-bibenzo[d]imidazole molecules and how their arrangement changes with the increasing amount of PA in the system with the help of cluster analysis. From the molecular dynamics simulation conducted at different temperatures and phosphoric acid doping level, we have predicted the diffusion of phosphoric acid and monomer. As a dynamic quantity, we have also calculated ring flipping of the imidazole ring of the monomer.

Characterization of the structures and dynamics of phosphoric acid doped benzimidazole mixtures: a molecular dynamics study - More, Minal; Pahari, Swagata; Roy, Sudip; Venkatnathan, Arun (Journal of Molecular Modeling, 2013)
Benzimidazole-based polymer membranes like poly(2,5-benzimidazole) (ABPBI) doped with phosphoric acid (PA) are electrolytes that exhibit high proton conductivity in fuel cells at elevated temperatures. The benzimidazole (BI) moiety is an important constituent of these membranes, so the present work was performed in order to achieve a molecular understanding of the BI-PA interactions in the presence of varying levels of the PA dopant, using classical molecular dynamics (MD) simulations. The various hydrogen-bonding interactions, as characterized based on structural properties and hydrogen-bond lifetime calculations, show that both BI and PA molecules exhibit dual proton-acceptor/donor functionality. An examination of diffusion coefficients showed that the diffusion of BI decreases with increasing PA uptake, whereas the diffusion of PA slightly increases. The hydrogen-bond lifetime calculations pointed to the existence of competitive hydrogen bonding between various sites in BI and PA.
Keywords: Diffusion coefficient; Hydrogen bond; molecular dynamics; Radial distribution functions